Earth Sciences and Mathematics, Volume I - Camacho, Antonio G.; Camacho, Antonio G.; Díaz, Jesús I.; Díaz, Jesús I.; Fernández, José.; Fernández, José. (Pageoph Topical Volumes, 2008)
A Complutense International Seminar on "Earth Sciences and Mathematics" was organised and held in Madrid at the Facultad de Ciencias Matemáticas of the Universidad Complutense de Madrid September, 13th-15th, 2006. Scientists from both fields, Mathematics and Earth Sciences, took part in this International Seminar, addressing scientific problems related with our planet from clearly complementary approaches, seeking to gain and learn from this dual approach and proposing a closer collaboration in the near future. This volume is the first one of a Topical Issue on "Earth Sciences and Mathematics" and contains papers addressing different topics as deformation modelling applied to natural hazards, inverse gravimetric problem to determine 3D density structure, advanced differential SAR interferometry, climate change, geomagnetic field, Earthquake statistics, meteorological studies using satellite images, climate energy balance models, study of soils properties, and multifractal data sets.